Using Qualitative Indicators in Infrastructure Assessment Using the Functionality–Resiliency–Sustainability Framework - Upadhyaya, Jyoti Kumari; Biswas, Nihar; Tam, Edwin K. L. (Frontiers in Sustainable Cities, 2021)
This paper presents the implementation of decision criteria template to incorporate qualitative indicators in functionality, resiliency and sustainability assessments of stormwater infrastructure using the Functionality-Resiliency-Sustainability Framework. Qualitative attributes, even though deemed important, are usually not included, or adequately considered because of their inherent subjectivity associated with assessing them. Whenever qualitative indicators are used in practice, an ordinal scale such as poor, fair, good, very good is often applied. Depending on the understanding and priorities of the evaluator, the meaning of poor, fair, good and very good score can differ significantly. Such indicators were often not intended to facilitate engineering solutions but rather management related concerns. However, understanding the issues behind using qualitative measures is critical for stormwater infrastructure because many non-conventional indicators - which are often frequently nontechnical measures – can be used to assess the resiliency and sustainability of stormwater system. Moreover, there are often few resources to adapt specific qualitative factors to quantitative equivalents. To address this gap, a decision criteria template is developed to score qualitative indicators within a multi-criteria assessment approach so that consistency, transparency and subjectivity in the assessment can be addressed. The indicator scoring template is illustrated in an example stormwater system in city of Windsor, Ontario, Canada.